Mathematical Modeling for Asthma due to Air Pollution - Shah, Nita H.; Suthar, Ankush H.; Pandya, Purvi M. (Journal of Applied Nonlinear Dynamics, 2026)
The human respiratory and cardiovascular systems get affected from surrounding atmosphere. Systematic study of indoor and outdoor pollution is needed for better understanding of their global epidemiology. In this substantial body of research, a mathematical model for transmission of asthma in a variable size population under the effects of indoor smoke and outdoor air pollution is proposed. In addition, the reproduction number for the dynamical system is formulated which signifies the intensity of asthma exacerbation. The global and local stability of acquired equilibrium points is studied. The performance of the model is simulated numerically which illustrates how polluted environment effectively increases levels of aeroallergens and their effect on asthma exacerbation, and how such exposures can be meaningfully reduced.